Post-operative analgesia in odontectomy: the efficacy of2% lidocaine with 1:80,000 epinephrine vs. 2% lidocaine with 1 80,000 epinephrine plus clonidine - Locsin, Ana Ramona S.
This study aimed to determine the effectivity of clonidine as a local anesthetic additive in prolonging local anesthesia as compared to 2% lidocaine with 1:80,000 epinephrine in odontectomy. Two patients with a dental diagnosis of asymptomatic mandibular third molar impaction and belonging to the ASA physical status Ml were the subjects of the study. The patient on which lidocaine alone was used as an anesthetic was designated as the control subject while the patient injected with lidocaine plus clonidine was designated as the experimental subject. Both subjects were given questionnaires and charts to be answered after surgery. The subjects were asked to tabulate pain scores in the given charts every 24 hours after odontectomy until pain was no longer felt. Both subjects experienced certain degrees of post-operative pain and anesthesia. It was also found that the experimental subject experienced longer post-operative anesthesia.